Effects of early parenteral iron combined erythropoietin in preterm infants: A randomized controlled trial. Issue 9 (March 2017) - Qiao, Linxia; Tang, Qingya; Zhu, Wenying; Zhang, Haiyan; Zhu, Yuefang; Wang, Hua
Abstract: Backgroud: The aim of the study was to evaluate the effect of early parenteral iron supplementation combined erythropoietin for prevention of anemia in preterm infants. Methods: In total, 96 preterm infants were randomly assigned to 3 groups: a control group receiving standard parenteral nutrition (group 1: n = 31), an iron-supplemented group (group 2: IS, n = 33), and an iron-supplemented combined erythropoietin group (group 3: IS+EPO, n = 32). The primary objective was to assess hemoglobin (Hb) levels. The secondary objectives included assessment of red blood cell counts (RBC), mean cell volume (MCV), serum iron, ferritin, percentages of reticulocyte (RET), total iron binding capacity (TIBC) and oxidative stress, which was assessed by measuring plasma levels of malondialdehyde and superoxide dismutase at baseline and at 2 weeks. The blood routine indices including Hb, RBC, MCV, and percentages of RET were measured at corrected age of 1 and 3 months. Results: At 2 weeks of life, the percentages of reticulocyte in group 2 and group 3 were significantly higher than those in group 1 (2.1±0.4, 2.5±0.3, and 1.7±0.3, respectively, P  < 0.001, P <0.001), whereas TIBC were significantly lower than those in group 1 (36.7±4.6, 36.0±4.7, and 41.6 ± 5.2 respectively, P  = 0.011, P  = 0.006). There were no significant differences in RBC counts, the levels of hemoglobin, ferritin, malondialdehyde, and superoxide dismutase among the 3 groups at 2weeks of life. RBC, Hb, MCV, body weight, body length, and head circumference at a corrected age of 1 month did not differ among 3 groups. At corrected age of 3months, more infants in the control group had abnormal Hb and MCV levels (Hb levels: 114.3 ± 21.3, 123.7 ± 31.6, and 125.1 ± 21.2, P  = 0.021, P  = 0.034, respectively; MCV: 74.1 ± 3.5, 78.3 ± 4.7 and 79.1 ± 5.2, P  = 0.017, P  = 0.012, respectively), whereas cases of oral iron, cases of breastfeeding, RBC, body weight, body length, and head circumference were not different among 3 groups. Conclusion: Early parenteral iron supplementation combined erythropoietin in preterm infants improved the percentages of reticulocyte, decreased total iron binding capacity, and improved the Hb and MCV levels at 3 months of age. Early parenteral iron supplementations with EPO were beneficial for the preterm infants.